The Effect of the Photoperiod on the Fatty Acid Profile and Weight in Hatchery-Reared Underyearlings and Yearlings of Atlantic Salmon Salmo salar L. - Nemova, Nina N. (Biomolecules, 2020)
The influence of two light regimes, 16:8 h light/dark (LD 16:8) and 24:0 h light/dark (LD 24:0), in comparison to a usual hatchery light regime (HL), on the fatty acids content and weight gain in hatchery-reared underyearlings (at 0+ age) and yearlings (at 1+ age) of Atlantic salmon in the summer–autumn period was studied. The total lipids were analyzed by Folch method, the lipid classes using HPTLC, and the fatty acids of total lipids using GC. The increase in EPA and DHA observed in October in underyearlings and yearlings salmon (especially under LD 24:0) suggests they were physiologically preparing for overwintering. The changes in fatty acids and their ratios in juvenile Atlantic salmon can be used as biochemical indicators of the degree to which hatchery-reared fish are ready to smoltify. These associated with an increase in marine-type specific DHA and EPA, an increase in the 16:0/18:1(n-9) ratio, in correlation with a reduction in MUFAs (mainly 18:1(n-9)). These biochemical modifications, accompanied by fish weight gain, were more pronounced in October in yearlings exposed to continuous light (LD 24:0). The mortality rate was lower in experimental groups of underyearliings with additional lighting. Exposure to prolonged and continuous light did not affect yearlings mortality rate.